Andaman Island and the historicity of colonial violence: an ecocritical study of Uzma Aslam Khan’s the miraculous true history of Nomi Ali - Rabani, Ghulam; Mishra, Binod (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study engages with the historical understanding of colonial violence followed by environmental disasters during World War II on Andaman Island. In the mid-twentieth century, the residents of Andaman Island were caught up in a battle between the British and the Japanese empires. These colonisers enslaved the locals, grabbed their land, and pillaged the natural resources. Instead of learning from the indigenous people who had established a community without disrupting the balance of nature, they continued to distract nature and enslavement of the local inhabitants. This research examines a central theme of environmental violence inherent to the colonial project through the shared heterogeneous experience of the Aboriginals. By employing the concept of ‘environmental violence’, this study critiques the violence sabotaged by British and Japanese colonisers to determine the changes in the lives of the fictional characters in Khan’s novel. The findings reveal that Uzma Aslam Khan’s The Miraculous True History of Nomi Ali (2019) might be better considered the historical colonial violence and the rights of the Indigenous people on Andaman Island are the critical components of the activist campaign for the return of their culture, history, and lands. It further reveals that colonial violence is responsible for the perpetuation of recent environmental disasters on Andaman Island.